Integrating holland's career theory: implementation patterns and challenges in school career guidance services - Faizal Nur; Sudarwan Danim; Nurul Astuty Yensy; I Wayan Dharmayana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study employed a concurrent mixed-methods design to examine Holland’s RIASEC implementation among 33 school counselors affiliated with MGBK SMA Pringsewu across ten senior high schools in Pringsewu Regency, Lampung. Data were collected through semi-structured interviews, questionnaires, and field observations, and analyzed using reflexive thematic analysis with quantitative integration. Three implementation patterns emerged: structured (27%), informal (55%), and nominal (18%). Counselor staffing level was strongly associated with implementation depth (ρ = 0.74, p < .01), while counselors with external RIASEC training demonstrated higher implementation scores (M = 4.0 vs. 2.6; d = 1.31), although training and adequate staffing co-occurred. Key barriers included the lack of a validated Bahasa Indonesia RIASEC instrument, limited theory-focused professional development, and role overload in single-counselor schools. Cultural adaptations involving family decision-making, Islamic vocational ethics, and local occupational examples were practiced independently but remained undocumented. Overall, the findings indicate that implementation fidelity depends not only on theoretical knowledge but also on adequate structural conditions and culturally responsive resources.